Development of an evaluation method to determine cavitation inception speed with aft hull vibration using kurtosis of the DEMON spectrum. (15th March 2018) - Han, Hyung Suk; Lee, Chang Noh; Jeon, Soo Hong; Lee, Kyoung Hyun; Park, Sung Ho
Abstract: The cavitation inception speed (CIS) is very important capability for a navy vessel because the underwater radiated noise dramatically increases when cavitation occurs. Therefore, the CIS has been severely restricted and evaluated at sea trial test steps in the shipbuilding process. After a naval vessel is delivered to the navy, CIS can vary according to the propeller and sea state conditions. However, inspection of CIS cannot be performed frequently due to time and expense limitation. Therefore, real time monitoring of CIS is urgently required by navy personnel. In order to inspect CIS with real time monitoring technique, the measuring method detecting fluctuation pressure of the propeller in a ship at sailing state should be developed. In this research, CIS monitoring techniques using acceleration on the hull above the propeller that can measure the fluctuation pressure of the propeller indirectly are suggested and verified experimentally. In addition, the evaluation algorithm of CIS using the kurtosis of the Detection of Envelope Modulation on Noise (DEMON) spectrum is used to determine the CIS quantitatively. Highlights: Cavitation Inception Speed monitoring techniques are studied with the acceleration on the hull above propeller. Kurtogram is used to determine the center frequency of the band-pass filter to obtain DEMON spectrum. Quantitatively evaluating logic of Cavitation Inception Speed using the kurtosis of DEMON is suggested.